Causal factors in the development of thoracic aortic aneurysm - E. B. Luneva; V. E. Uspenskyi; L. B. Mitrofanova; M. I. Paidimirova; A. V. Kandinskyi; E. V. Zemtsovsky (Российский кардиологический журнал, 2013)
Aim. To assess the causal factors in the development of thoracic aortic aneurysm. Despite the existing screening programmes, widely used visualisation methods, and improved intervention techniques, aortic aneurysm remains one of the leading causes of sudden cardiac death. The existing evidence on the causal factors in the development of thoracic aortic aneurysm is contradictory. Material and methods. We analysed medical histories of the patients hospitalized for thoracic aortic stenting from early 2011 to May 1 2012. The age and gender composition of the sample and the main causal factors resulting in the development of thoracic aortic aneurysm were assessed. Results. In total, 90 patients underwent thoracic aortic stenting. The main causes for the development of thoracic aortic aneurysm were: bicuspid aortic valve (n=30, 34%), atherosclerosis (n=30, 34%), and Marfan syndrome (n=10, 95). In 45 intraintervention biopsy samples, cystic medial necrosis was found in 55%, atherosclerosis in 27%, and normal tissue in 15% (n=12). Conclusion. The most common concomitant pathology in patients with thoracic aortic aneurysm was bicuspid aortic valve, aortic atherosclerosis, and hereditary connective tissue disorders. The main causal factor in the development of thoracic aortic aneurysm was cystic medial necrosis.